Community development and sustainable livelihoods of artisanal and small-scale tin mining (study of the implication of Law No.4/2009 on Mineral Mining and Coal in West Bangka Regency, Bangka Belitung Islands) - Indah, Gusti (Jurnal Administrasi Publik, 2017)
This paper attempts to investigate the community development and sustainable livelihoods of Artisanal and Small-Scale Mining (ASM) community under the Law No.4/2009 on Mineral Mining and Coal in West Bangka Regency. Qualitative method was used as research method with interviews, observations and document analysis were used in data collection stage. This results has confirmed some important facts about community development and sustainable livelihoods of ASM. Firstly, the existing condition of Sustainable Livelihood Capitals of ASM are poverty-driven and weaker long-term economic growth. Secondly , it is divided into three categories why community development of tin miners are not successful until now – social, governance, and economic constraints. To conclude, different levels of government are trying to meet the demands of ASM community’s interest, but a coordinated response has not been formulated.